Microfluidic system evaluation for the semi-automatic detection of MOG-IgG in serum samples - Numfon Khemthongcharoen; Panapat Uawithya; Nutthapon Yookong; Mayuree Chanasakulniyom; Wutthinan Jeamsaksiri; Witsaroot Sripumkhai; Pattaraluck Pattamang; Ekachai Juntasaro; Nongluck Houngkamhang; Therdthai Thienthong; Chamras Promptmas (My University, 2021)
Myelin oligodendrocyte glycoprotein reactive immunoglobulin G antibody (MOG-IgG) is in patients with central nervous system demyelination. Reliability of the conventional detection method relies on technician skills and pipetting error accumulation. This work develops a microfluidic system for semi-automatic MOG-IgG detection using cell-based immunofluorescence (IF) assay. The polydimethylsiloxane (PDMS) microfluidic was modified by poly-l-lysine to enhance the adhesion of Human embryonic kidney (HEK) cell. The untransfected and GFP-MOG transfected HEK cells were cultured, fixed, and stained in the microfluidic with the feeding reagents regulated by a syringe pump. Cell characterization, limit of detection (LOD), and turnaround time of the IF assay operation in microfluidic were compared to those in standard microplate. In microfluidic, cell-clumping formation can be avoided and thus signal variations that are caused by cell overlapping can be significantly reduced. LOD of MOG-IgG detection in the microfluidic is at least 2.5 times better than that in the microplate. Signal intensities of the IF staining for 1 h in microfluidic are comparable to those stained for overnight in the standard microplate. By integration with a serial dilution microfluidic, the optimal cutoff titer for MOG-IgG positivity in the patient samples was determined by Receiver operating characteristic curve (ROC) analysis.
Keywords: HEK 293 cells; Pipette; Microfluidic and Bio-sensing Technologies